Comprehensive analysis of SLC43A2 on the tumor immune microenvironment and prognosis of liver hepatocellular carcinoma - Liao, Yan; Weng, Junmei; Chen, Lian; Hu, Nan; Yuan, Xun; Wang, Jianhua; He, Feng; Cai, Yixin; Huang, Qin; Wang, Jianing; Huang, Liu (Frontiers in Genetics, 2022)
Abstract Background Tumor cells overexpressed SLC43A2 to outcompete T cells for methionine, which resulted in T cell exhaustion. We explored the influence of SLC43A2 related IRG on the immune infiltrates' abundances and survival of LIHC patients. Methods The TCGA-LIHC dataset (n = 374) was used as testing cohort and the LIRI-JP dataset (n=231) as validation cohort. IRGs were obtained from the ImmPort. Statistical analyses were performed with R (V 4.0.5). Online databases such as GEPIA, GSCALite, The Kaplan Meier plotter, STRING, KEGG, TIMER2 and CMap were used for differential expression, immune infiltration, functional enrichment, survival and drug-induced gene perturbation analysis. Results Higher SLC43A2 expression was found in tumor tissues and significantly correlated with worse survival in LIHC (all P < 0.05). More CD4+ T cell, Tregs, Macrophage, MDC, and MDSC were infiltrated in LIHC patients with high SLC43A2 expression, but less naive CD8+ T cell, Endothelial cell, and Hematopoietic stem cell were. SLC43A2 was positively correlated with immune-depleted markers (all P < 0.001). Based on its related IRGs, we constructed and validated a prognostic risk score model. Arachidonic acid, SB-202190 and guanethidine were identified as possible immunomodulators for LIHC. Conclusions SLC43A2 governed suppressive immune cells infiltration to LIHC. A new risk score model based on SLC43A2 related IRGs could identify patients at higher risk in LIHC. Arachidonic acid, SB-202190 and guanethidine might act as immunomodulators for LIHC via interfering with SLC43A2 and need to be studied in the future.